Identification of the Tyrosine- and Phenylalanine-Derived Soluble Metabolomes of Sorghum - Simpson, Jeffrey P.; Olson, Jacob; Dilkes, Brian; Chapple, Clint (Frontiers in Plant Science, 2021)
The synthesis of small organic molecules, known as specialized/secondary metabolites, is one mechanism by which plants resist and tolerate biotic and abiotic stress. Many specialized metabolites are derived from the aromatic amino acids phenylalanine (Phe) and tyrosine (Tyr) and improved characterization of compounds derived from these amino acids would inform strategies for developing crops with greater resilience and improved traits for the biorefinery. Sorghum and other grasses possess PHE AMMONIA-LYASE (PAL) enzymes that generates cinnamic acid from Phe, and bifunctional PHE/TYR AMMONIA-LYASE enzymes (PTAL,), that generates cinnamic acid and p-coumaric acid from Phe and Tyr, respectively. Cinnamic acid can, in turn, be converted to p-coumaric acid by CINNAMATE 4-HYDROXYLASE. Thus, Phe and Tyr are both precursors of common downstream products. Not all derivatives of Phe and Tyr are shared and each can act as the precursor for unique metabolites. In this study, we used 13C isotopic labeled precursors, and our recently developed PODIUM mass spectrometry (MS) analytical pipeline, to identify over 600 MS features derived from Phe and Tyr in sorghum. These features comprised 20 percent of the MS signal collected by reverse-phase chromatography and detected through negative-ionization. Ninety percent of the labeled mass features were derived from both Phe and Tyr, although the proportional contribution of each precursor varied. Additionally, the relative incorporation of Phe and Tyr varied between metabolites and tissues, suggesting the existence of multiple pools of p-coumaric acid that are fed by the two amino acids. Phe incorporation was greater for many known hydroxycinnamate esters and flavonoid glycosides. In contrast, mass features derived exclusively from Tyr were the most abundant in every tissue. The Phe- and Tyr-derived metabolite library was also utilized to retrospectively annotate soluble MS features in two brown midrib mutants (bmr6 and bmr12), identifying several MS features that change significantly in each mutant.